(untitled) (Third Sector Social Economic Review, 2026)
In today’s globalization of markets, international commercial and financial relations are developing and as a result, public and private sector institutions are seeking ways to obtain the loans they need from domestic or foreign markets. The countries resort to external borrowing when they cannot obtain the resources they need from domestic markets to carry out their activities. This situation causes countries’ external debts to increase. Currently, the issue of external debt has become a significant problem not only for developing countries but also for developed countries. The purpose of this study is to assess Turkey’s debt situation in comparison to G-7 countries by comparing the external debts of Turkey, which is among the developing countries and striving to reach the category of developed countries. Within this perspective, the indebtedness of countries has been analysed primarily based on the ratios of total external debt to Gross Domestic Product, total external debt to exports, and international reserves to total external debt. In addition, based on the available data, panel data analysis was also conducted to investigate the sustainability of countries’ external debt. The research concluded that, according to the criteria determined by the World Bank, Turkey is in a better position than the G-7 countries, that the external debt burden of the G-7 countries continues to increase, and that countries need to implement policies that encourage exports in order to reduce their debts. This study is original in that it evaluates and compares the external debt of the G-7 countries and Turkey according to ratios and panel data analysis, and is therefore believed to contribute to the literature.